CLIMATE JUSTICE AND SOCIAL EQUITY IN INDONESIAN WATERSHED GOVERNANCE : THE CASE OF CITARUM - Putri, Sapen Sartika Unyi; Widianingsih, Ida; Dewi, Anggia Utami (Sosiohumaniora, 2024)
This study explores how climate justice and social equity are integrated into watershed governance in Indonesia, using the Citarum River as a case study. It examines the progress and challenges faced by local communities and the government, as well as the policies implemented to achieve climate justice and social equity within a sustainable governance framework. Using a case study approach and qualitative methods, the findings highlight progress through initiatives such as the Citarum Harum program, which has facilitated renewable energy transitions, ecological restoration, and the adoption of Natural Climate Solutions (NCS), including the Citarum Living Lab program. However, findings also reveal that several challenges persist, including socio-political barriers, participatory limitations (especially from marginalized communities and non-governmental actors in decision-making), fragmented policy coordination, lack of stakeholder synergy, overlapping policies leading to inefficiencies, unequal resource distribution, and the increasing frequency of natural disasters that hinder inclusive governance. This study underscores the critical importance of integrating climate justice and social equity into Citarum Watershed governance to achieve environmental sustainability and improve the quality of life for local communities. It emphasizes the need to strengthen collaborative governance models, particularly through the Quintuple Helix framework, while ensuring inclusive decision-making. The findings provide valuable insights for policymakers to frame climate crises through the lens of climate justice and social equity, ensuring that sustainable watershed governance not only benefits communities in the Citarum Watershed but also contributes to broader societal well-being.